2012
DOI: 10.1097/opx.0b013e31826c6508
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Intermittent Air Exposure on Lipid Deposition

Abstract: This study found that lipid deposition profiles are CL material dependent and that intermittent air exposure can influence the mass of lipid deposited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 30 publications
0
39
0
Order By: Relevance
“…The limitations of the conventional vial model have been recognized by researchers, and attempts have been made to create unique in vitro eye models simulating the ocular environment, by including a microfluidic tear replenishment component [20][21][22][23][24] and/or intermittent air exposure. 25,26 Not surprisingly, the results generated from these experiments are very different than those obtained with the conventional vial model, and may more closely resemble in vivo data. [20][21][22][23][24][25] Thus, developing an intricate in vitro eye model to examine CLs will provide new insights on the interaction of lens materials with the ocular surface, and help facilitate the development of new materials and new applications for CLs in the coming decades.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…The limitations of the conventional vial model have been recognized by researchers, and attempts have been made to create unique in vitro eye models simulating the ocular environment, by including a microfluidic tear replenishment component [20][21][22][23][24] and/or intermittent air exposure. 25,26 Not surprisingly, the results generated from these experiments are very different than those obtained with the conventional vial model, and may more closely resemble in vivo data. [20][21][22][23][24][25] Thus, developing an intricate in vitro eye model to examine CLs will provide new insights on the interaction of lens materials with the ocular surface, and help facilitate the development of new materials and new applications for CLs in the coming decades.…”
Section: Discussionmentioning
confidence: 63%
“…25,26 Not surprisingly, the results generated from these experiments are very different than those obtained with the conventional vial model, and may more closely resemble in vivo data. [20][21][22][23][24][25] Thus, developing an intricate in vitro eye model to examine CLs will provide new insights on the interaction of lens materials with the ocular surface, and help facilitate the development of new materials and new applications for CLs in the coming decades.…”
Section: Discussionmentioning
confidence: 63%
“…Pucker and colleagues 18 also examined the in vitro uptake of lipids, exposing the lens materials to straight lipid solutions, showing higher uptake rates than reported in this article. 54 Other differences in ATS concentrations, measuring techniques, examined lipids, incubation solution, incubation volumes, and replenishment rates influence the degree of cholesterol uptake and make direct comparisons between experiments difficult. 18 It also differs from the ex vivo study of Maziarz et al, 28 in that our lenses were not exposed to the atmosphere during blinking, and recent work from our laboratory has shown that drying of the lens surface during the interblink period does increase lipid deposition.…”
Section: Discussionmentioning
confidence: 99%
“…A few previous publications hinted that care solutions may have a role in removal of lipids from contact lenses [15,22]. Thus it seems feasible that they could also play a prophylactic role in reducing lipid sorption.…”
Section: Sorption Without and With Prior Mps Exposurementioning
confidence: 97%